2009
DOI: 10.1097/qad.0b013e328322ffac
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the current global burden of cryptococcal meningitis among persons living with HIV/AIDS

Abstract: This study, the first attempt to estimate the global burden of cryptococcal meningitis, finds the number of cases and deaths to be very high, with most occurring in sub-Saharan Africa. Further work is needed to better define the scope of the problem and track the epidemiology of this infection, in order to prioritize prevention, diagnosis, and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
1,578
7
67

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,877 publications
(1,665 citation statements)
references
References 41 publications
13
1,578
7
67
Order By: Relevance
“…grubii (16,24,25,34). Even though cryptococcosis in patients with impaired immunity is rarely caused by serotype B, in this study we found 2 patients with AIDS, and in the period 1997-2005, 1 of the 30 cases caused by C. gattii had HIV infection (16).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…grubii (16,24,25,34). Even though cryptococcosis in patients with impaired immunity is rarely caused by serotype B, in this study we found 2 patients with AIDS, and in the period 1997-2005, 1 of the 30 cases caused by C. gattii had HIV infection (16).…”
Section: Discussionmentioning
confidence: 50%
“…The most important issue being highlighted by this study, is the high cryptococcocal morbidity in Colombia both in immunocompetent, as well as in immunosuppressed populations, illustrating that although advances in the antiretroviral therapy have occurred, cryptococcosis is still being diagnosed in Colombia and several other countries (16,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 83%
“…1 The development of cryptococcal meningitis occurs mainly in immunocompromised HIV-1-infected patients, most likely by reactivation of latent pulmonary C. neoformans infection. 2 It is estimated that 504,000 HIV-1-infected patients die every year from cryptococcal meningitis in sub-Saharan Africa, 3 which surprisingly exceeds the annual death rate of tuberculosis-associated HIV cases. Resistance against C. neoformans primarily involves monocytic effector mechanisms.…”
mentioning
confidence: 99%
“…Cryptococcus is the most common cause of fungal meningitis and meningoencephalitis. Global estimates suggest that 1 million cases of cryptococcal meningitis occur each year, with approximately 600,000 fatalities [65]. CNS disease resulting from C. neoformans strains are most common in patients with advanced HIV, while C. gattii strains are emerging pathogens in immunocompetent individuals [66,67].…”
Section: Fungal: Cryptococcusmentioning
confidence: 99%